2020
DOI: 10.1111/cbdd.13671
|View full text |Cite
|
Sign up to set email alerts
|

Computational‐based discovery of FAK FERM domain chemical probes that inhibit HER2‐FAK cancer signaling

Abstract: The N-terminal FERM domain of focal adhesion kinase (FAK) contributes to FAK scaffolding and interacts with HER2, an oncogene and receptor tyrosine kinase. The interaction between HER2 and FAK drives resistance to FAK-kinase domain inhibitors through FAK Y397 transphosphorylation and FAK re-activation upon inhibition. As such, FAK FERM remains an attractive drug discovery target. In this report, we detail an alternative approach to targeting FAK through virtual screening-based discovery of chemical probes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The results were confirmed by biological assays such as phosphorylation, cellular localization and cellular invasion assays. VS-14 effectively blocked FAK auto-and transphosphorylation, disrupted HER2-FAK co-localization in cells and suppressed HER2-dependent cellular invasion (Stahl et al, 2020). This study identified a new chemical probe in the FAK FERM domain that warrants further investigation for its biological significance in cancer.…”
Section: Design Of Fak Inhibitorsmentioning
confidence: 86%
“…The results were confirmed by biological assays such as phosphorylation, cellular localization and cellular invasion assays. VS-14 effectively blocked FAK auto-and transphosphorylation, disrupted HER2-FAK co-localization in cells and suppressed HER2-dependent cellular invasion (Stahl et al, 2020). This study identified a new chemical probe in the FAK FERM domain that warrants further investigation for its biological significance in cancer.…”
Section: Design Of Fak Inhibitorsmentioning
confidence: 86%
“…(ii) The allosteric inhibitors of FAK are non-ATP-competitive compounds still undergoing pre-clinical investigation. Allosteric inhibitors have been developed that bind an allosteric site within the kinase domain, but, differently from the ATP-binding site, and seem to be highly specific to FAK [49][50][51][52]. These inhibitors induce an inactive conformation of the kinase domain, hampering interactions with receptor tyrosine kinases (RTKs) or auto-phosphorylation at Tyr397.…”
Section: Fak Inhibitorsmentioning
confidence: 99%
“…The FAK FERM domain serves as a scaffold to mediate protein-protein interaction and links signals from the extracellular compartment to the nucleus [36,37]. For instance, the FERM domain promotes the association of FAK with integrins and activated growth factor receptors and the membrane-cytoskeleton linker ezrin [38][39][40][41]. Recent computational tools have demonstrated that the FERM domain is also involved in the interaction of FAK with HER2 toward the resistance to FAK inhibitors [39].…”
Section: Fak Structural Organization and Activationmentioning
confidence: 99%
“…For instance, the FERM domain promotes the association of FAK with integrins and activated growth factor receptors and the membrane-cytoskeleton linker ezrin [38][39][40][41]. Recent computational tools have demonstrated that the FERM domain is also involved in the interaction of FAK with HER2 toward the resistance to FAK inhibitors [39]. Besides, the FERM domain may facilitate the translocation of FAK into the nuclear compartment, where FAK mediates the regulation of gene expression through the interaction with certain transcription factors and epigenetic modulators [42][43][44][45].…”
Section: Fak Structural Organization and Activationmentioning
confidence: 99%